2018
DOI: 10.1021/acs.inorgchem.7b02617
|View full text |Cite
|
Sign up to set email alerts
|

Combined Approach for the Structural Characterization of Alkali Fluoroscandates: Solid-State NMR, Powder X-ray Diffraction, and Density Functional Theory Calculations

Abstract: The structures of several fluoroscandate compounds are presented here using a characterization approach combining powder X-ray diffraction and solid-state NMR. The structure of KScF was fully determined from Rietveld refinement performed on powder X-ray diffraction data. Moreover, the local structures of NaScF, LiScF, KScF, and NaScF compounds were studied in detail from solid-state F andSc NMR experiments. The Sc chemical shift ranges for six- and seven-coordinated scandium environments were defined. TheF che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 51 publications
2
17
0
1
Order By: Relevance
“…To convert the calculated isotropic chemical shielding into isotropic chemical shift, the definition of calibration curve relating isotropic chemical shift and shielding is necessary. For 45 Sc and 19 F the relationship reported in our previous study [6] are : δiso = -0.852×σiso+667.42 and δiso = -0.589×σiso +20.24, respectively.…”
Section: Castep Calculationsmentioning
confidence: 72%
See 3 more Smart Citations
“…To convert the calculated isotropic chemical shielding into isotropic chemical shift, the definition of calibration curve relating isotropic chemical shift and shielding is necessary. For 45 Sc and 19 F the relationship reported in our previous study [6] are : δiso = -0.852×σiso+667.42 and δiso = -0.589×σiso +20.24, respectively.…”
Section: Castep Calculationsmentioning
confidence: 72%
“…We suppose that this is some unknown cesium fluoroscandates CsxScyFz. The chemical shift for the bridging fluorine atoms is ranging from -23 to -75 ppm [6], therefore, it can be concluded that each fluorine atom in the CsSc3F10 compound is bonded with two scandium atoms. respectively [6].…”
Section: X-ray Powder Diffraction and Nmr Spectroscopymentioning
confidence: 97%
See 2 more Smart Citations
“…X-ray powder diffraction characterization showed that EM has a distinct diffraction peak, compared with enrofloxacin, EM has the characteristics of diffraction peak in 2θ were 7.93, 9.61, 11.89, 22.07, 22.95, 23.68, 24.36, 24.97, 35.29, 35.97, respectively, indicating that it is a crystal. 37 In addition, the numbers of diffraction peaks of EM were greatly different from enrofloxacin, and the energetic peak of EM is less than that of enrofloxacin, indicating that EM crystals may have small particle size, which facilitates their rapid dissolution. The angular positions, and relative intensity, as well as the shape of the diffraction peaks of EM, are greatly different from enrofloxacin, indicating that mesylate and enrofloxacin are not a simple physical mixture, but mesylate reacts with enrofloxacin to form a crystal different from enrofloxacin.…”
Section: X-ray Powder Diffraction (Xrpd)mentioning
confidence: 99%